2010
DOI: 10.1103/physrevd.81.085007
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of restricted baby Skyrme models

Abstract: A restriction of the baby Skyrme model consisting of the quartic and potential terms only is investigated in detail for a wide range of potentials. Further, its properties are compared with those of the corresponding full baby Skyrme models. We find that topological (charge) as well as geometrical (nucleus/shell shape) features of baby skyrmions are captured already by the soliton solutions of the restricted model. Further, we find a coincidence between the compact or non-compact nature of solitons in the rest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
121
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 81 publications
(128 citation statements)
references
References 30 publications
7
121
0
Order By: Relevance
“…It has been previously found that the model preserves many properties of the original ungauged version [41][42][43]. First of all, there is a BPS bound which can be saturated by the corresponding BPS configurations.…”
Section: Jhep11(2014)095mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously found that the model preserves many properties of the original ungauged version [41][42][43]. First of all, there is a BPS bound which can be saturated by the corresponding BPS configurations.…”
Section: Jhep11(2014)095mentioning
confidence: 99%
“…In fact, there exists a (2 + 1) dimensional version of the Skyrme model, usually referred to as the baby Skyrme model, which supports solitonic solutions (baby skyrmions) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] (for the gauged version see [39,40]). This field theory also possesses its BPS limit, whose Lagrangian consists of the (2+1) dimensional version of the Skyrme term and a potential [41][42][43]. Moreover, there is again a gauged version of this model, the so-called gauged BPS baby Skyrme model, which has been analyzed recently in the case of an asymptotically vanishing magnetic field [44].…”
Section: Jhep11(2014)095mentioning
confidence: 99%
“…And, indeed, field theories based on versions of the above energy functional [7]- [15] are known to support both Bogomolnyi bounds and topological BPS solitons [10]- [15]. Among these BPS theories there are BPS submodels of some well-known and relevant non-linear field theories like, e.g., the Skyrme [16][17][18] and baby Skyrme [19][20][21][22][23] models or the abelian Higgs model, which makes them all the more interesting also from a phenomenological perspective (see, e.g., [24,25]).…”
Section: Jhep08(2013)062mentioning
confidence: 99%
“…ð4:29Þ which is closely related to the so-called BPS baby Skyrme model [27][28][29][30]. It consists of two parts, a fourth derivative term which has a vacuum at juj ¼ 1.…”
Section: Model and Bogomolny Equationmentioning
confidence: 99%